Sensing and Signaling in Antiviral Innate Immunity - BOWIE, ANDREW; O'NEILL, LUKE (My University, 2010)
Viruses are detected by the innate immune system, leading to the initiation of the anti-viral immune response via the production of type I interferons and inflammatory cytokines such as interleukin-1. Remarkable progress has been made over the past few years towards understanding the contribution of Toll-like receptors, RIG-I like receptors, NOD-like receptors and HIN-200 family members to viral detection. Furthermore, new complexities in the signaling pathways activated by these receptors continue to be revealed. Together, these new insights are leading to therapeutically useful information in the fight against viruses.
PUBLISHED
Keywords: immune system; Immunology, Inflammation & Infection